Psychological state and predictors of psychiatric morbidity in COVID-19 patients six weeks after discharge - GEÇER, EKMEL (My University, 2023)
To be able to detect possible psychological distress and long-term deterioration caused by COVID-19, following the patient, who has recovered, is crucial. Therefore, this study (i); aims to examine the ongoing fear-loss of control, the rate of anxiety, depression, and post-traumatic stress disorder levels following the 6th week after discharge; (ii) to examine the effect of post-traumatic stress disorder on anxiety, and depression and (iii) within the same context to reveal the developmental markers of psychiatric morbidity and the risk group. The study includes 180 patients who were hospitalized with COVID-19 diagnosis. Sociodemographic Data Form, the Hospital Anxiety Depression Scale and the Impact of Event Scale-Revised were used in the current study. High rates of symptoms of anxiety, depression, and PTSD were reported by the inpatients, as more than one-third scored above the anxiety and depression cut-off scores of borderline abnormal and abnormal. Also, 37.22 % of the participants reported the likely presence of PTSD symptoms. Anxiety and depression were significantly positively related to the symptoms of PTSD. The results suggest that there is psychiatric morbidity in anxiety, depression, and post-traumatic stress disorder and that especially posttraumatic stress poses a risk for other psychopathologies.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; Klinik Psikolojisi; Social Sciences and Humanities; Psychology; Social Psychology; Clinical Psychology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); PSİKOLOJİ, SOSYAL; PSİKOLOJİ, KLİNİK; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; PSYCHOLOGY, SOCIAL; PSYCHOLOGY, CLINICAL; Klinik Psikoloji; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities; COVID-19 pandemic; Anxiety; Depression; Post-traumatic stress disorder; Psychiatric morbidity